2014
DOI: 10.1155/2014/324509
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Internal Jugular Vein Thrombosis Leading to Diagnosis of Bilateral Ovarian Ependymoma

Abstract: Ovarian ependymomas are extremely rare tumors of the ovary. We present a case of a 67-year-old lady presented to us with swelling in the right side of neck for 2 months followed by pelvic pain, lower abdominal distention, and weight loss for 1 month. Her coagulation profile, blood chemistry, lipid profile, and tumor markers were within normal limits. Neck Doppler ultrasonography revealed thrombus in the right internal jugular vein and CT scan of the abdomen showed bilateral ovarian masses. Patient was subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In previous reports most patients with early stage received operation only [3,5,8] while patients with advanced stage administrated with adjuvan radiation and/or chemotherapy after cytoreductive surgery [1,3,6,7]. Patients with early stage have longer overall survival with less recurrence rates, so stage seems to be the most important prognostic parameter of survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports most patients with early stage received operation only [3,5,8] while patients with advanced stage administrated with adjuvan radiation and/or chemotherapy after cytoreductive surgery [1,3,6,7]. Patients with early stage have longer overall survival with less recurrence rates, so stage seems to be the most important prognostic parameter of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Ependymomas are an infrequent glial tumors that usually originate from the central nervous system, but they can occasionally occur in various extra-axial regions [1,2]. Pure ovarian ependymoma, classified as differentiated glioma, was first described by Kleinman et al in 1984 [3] and only a few cases have been reported since then.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate recognition of the syndrome is important because VTE often requires careful medical surveillance and management. 9 Internal jugular vein thrombosis is a rare vascular disease that can be overlooked or misdiagnosed. 10 It most commonly occurs in persons with intravenous drug abuse or patients with prolonged central venous catheterization due to iatrogenic trauma.…”
Section: Discussionmentioning
confidence: 99%